2007
DOI: 10.1111/j.1365-3059.2007.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of black foot disease in grapevine nurseries

Abstract: Black foot disease of grapevines is a decline and dieback disease caused by a soilborne pathogen complex including Cylindrocarpon liriodendri , C. macrodidymum , Campylocarpon fasciculare and Campyl. pseudofasciculare . These pathogens cause primary infections of roots and basal ends of grafted cuttings in nursery soils. Thirteen fungicides were screened in vitro for mycelial inhibition of these pathogens. Prochloraz manganese chloride, benomyl, flusilazole and imazalil were the most effective fungicides teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
193
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(201 citation statements)
references
References 17 publications
6
193
0
2
Order By: Relevance
“…Samuels and Brayford (1990) commented on the morphological variation in collections of I. radicicola and its anamorph "C." destructans. Seifert et al (2003) showed that there was more than one "C." destructans-like species occurring on Panax, and that none of the resolved clades correlated to the ex-type strain of I. radicicola, leading Halleen et al (2006) to question the purported anamorph/teleomorph link between I. radicicola (from Cyclamen, Sweden) and "C." destructans (from Panax, USA). Based on a phylogenetic analysis of ITS nrRNA gene sequences, Schroers et al (2008) concluded that the I. radicicola complex includes "C." destructans, "C." destructans var .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Samuels and Brayford (1990) commented on the morphological variation in collections of I. radicicola and its anamorph "C." destructans. Seifert et al (2003) showed that there was more than one "C." destructans-like species occurring on Panax, and that none of the resolved clades correlated to the ex-type strain of I. radicicola, leading Halleen et al (2006) to question the purported anamorph/teleomorph link between I. radicicola (from Cyclamen, Sweden) and "C." destructans (from Panax, USA). Based on a phylogenetic analysis of ITS nrRNA gene sequences, Schroers et al (2008) concluded that the I. radicicola complex includes "C." destructans, "C." destructans var .…”
Section: Introductionmentioning
confidence: 99%
“…Cylindrocarpon and Cylindrocarpon-like species have since been commonly associated with root and decay of woody and herbaceous plants (Domsch et al 2007). Cylindrocarpon root rot causes losses up to 30% on ginseng (Panax quinquefolium) (Seifert et al 2003), and plays an important role in black foot rot of grapevines (Halleen et al 2004(Halleen et al , 2006, apple replant disease (Tewoldemedhin et al 2010), and beech cankers (Castlebury et al 2006), to name but a few hosts of economic importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, HWT is performed in two periods: before grafting (FOURIE; HALLEEN, 2004a), and after collection of cuttings from the nursery and before planting in the vineyard (HALLEEN et al, 2007). Gramaje et al (2009) observed that the mycelial growth of Cadophora luteo-olivaceae isolates was not viable from 50ºC to 54ºC for 30 minutes, but Cylindrocarpon liriodendri and Cylindrocarpon macrodidymum isolates were already unviable from 43ºC to 47ºC.…”
Section: Advances Observed In the Management Of New Diseasesmentioning
confidence: 99%
“…In addition to these species, new genera have been continuously reported in literature. HALLEEN et al (2007) conducted pathogenicity studies in nurseries and vineyards with declining plants and found that symptomatic plants were contaminated by Cadophora luteo-olivaceae, Phialemonium cf. curvatum and Pleurostomophora richardsiae, whereas Moyo et al (2014) identified species of arthropods also acting in the transmission of trunk diseases.…”
Section: New Diseases Transmitted By Vegetative Propagationmentioning
confidence: 99%